Assessing the Impact of Automated Dispensing Systems on Medication Safety and Workflow Efficiency in Hospital Pharmacies - Ruslan, Hardiyanti; Musfirah, Nurul; Rahmi, Rahmi (ScieClouds Publishing, 2024)
This study evaluated the impact of Automated Dispensing Systems (ADS) on medication safety and workflow efficiency in hospital pharmacies. A quasi-experimental design was employed, comparing pharmacy operations before and after the implementation of ADS in a tertiary care hospital. Data were collected from 50 pharmacy staff members and secondary data on medication errors and workflow efficiency, with operational metrics such as dispensing time, error rates, and prescription processing rates. The results indicated a 77.1% reduction in medication errors, with significant improvements in the accuracy of drug dispensing, dosage, and labeling. Additionally, workflow efficiency was enhanced, with dispensing times reduced by an average of 7.4 minutes per prescription, and the number of prescriptions processed per hour increased by 60%. Paired t-tests, regression analysis, and ANOVA tests were used to analyze the data, revealing that ADS adoption led to measurable improvements in both safety and efficiency. The study further found that pharmacist training and system readiness were critical factors in maximizing these benefits. These findings suggest that ADS technology can significantly improve medication safety by reducing errors and enhancing workflow, offering valuable insights for hospitals considering the implementation of automated systems. This research fills a gap in existing literature by providing empirical data on the specific impact of ADS on different types of medication errors and by offering a comprehensive analysis of both operational metrics and staff perceptions.